Assessing Devolution in the Canadian North: A Case Study of the Yukon Territory - Alcantara, Christopher; Cameron, Kirk; Kennedy, Steven (ARCTIC, 2012)
Despite a rich literature on the political and constitutional development of the Canadian territorial North, few scholars have examined the post-devolution environment in Yukon. This lacuna is surprising since devolution is frequently cited as being crucial to the well-being of Northerners, leading both the Government of Nunavut and the Government of the Northwest Territories to lobby the federal government to devolve lands and resources to them. This paper provides an updated historical account of devolution in Yukon and assesses its impact on the territory since 2003. Relying mainly on written sources and 16 interviews with Aboriginal, government, and industry officials in the territory, it highlights some broad effects of devolution and specifically analyzes the processes of obtaining permits for land use and mining. Our findings suggest that devolution has generally had a positive effect on the territory, and in particular has led to more efficient and responsive land use and mining permit processes. Malgré le grand nombre de publications au sujet du développement politique et constitutionnel du Nord territorial canadien, peu d’érudits ont étudié la période ayant suivi le transfert des responsabilités au Yukon. Cette lacune surprend car le transfert des responsabilités est souvent cité comme étant crucial au bien-être des gens du Nord, ce qui a incité tant le gouvernement du Nunavut que celui des Territoires du Nord-Ouest à exercer des pressions sur le gouvernement fédéral en vue du transfert des terres et des ressources. Cet article présente l’historique actualisé du transfert des responsabilités au Yukon et évalue ses incidences sur le territoire depuis 2003. Il s’appuie principalement sur des sources écrites et sur 16 entrevues avec des Autochtones, des représentants des gouvernements et des représentants d’industries du territoire pour mettre en évidence certains effets à grande échelle du transfert des responsabilités et analyser plus précisément les processus d’obtention de permis en vue de ...